Soil fertility management on small farms in Africa: Evidence from Nakuru district, Kenya - Omamo, Steven Were; Williams, J.C.; Obare, G.A.; Ndiwa, Nicholas N. (Elsevier, 2002)
This paper uses data from a 1998 survey of farming households in Nakuru district, Kenya to explore factors influencing soil fertility management decisions of smallholder farmers in Africa. The modeling strategy builds on results of research in soil science that point to the joint determination of inorganic and organic soil nutrient stocks and flows on-farm. Farmers' decisions on levels of inorganic and organic fertilizer use are hypothesized to be similarly mutually dependent, and to be further influenced by various farmer-specific socioeconomic factors. Econometric estimations indicate that once the effects of cropping patterns, farm-to-market transport costs, and labor availability are taken into account, smallholder applications of inorganic and organic fertilizers appear to be substitutes. Implications for research and policy are drawn.